Dying For Faith, Transforming Memories: Chinese Christian Martyr Watc hman Nee (1903–1972) (The Macau Ricci Institute Journal, 2020)
Martyrdom is an integral part of the narrative of all three monotheistic religions. This article draws on the story of Watchman Nee (Ni Tuosheng 倪柝声, 1903–1972) to investigate the meaning of martyrdom in Chinese Protestant Christianity. When countries in East Asia developed into centralized nation-states, some of the governments often perceived Christianity as subversive and mobilized official resources to marginalize, persecute and destroy indigenous Christian communities. Watchman Nee, who founded an indigenous Protestant movement in the early 20th century, was arrested in 1952 and died in a labour camp in 1972. His story reveals his consistent efforts to invoke Christian transcendental ideas against the state’s antireligious measures and to recast the traumatic experience of persecution as a spiritual struggle. Even in the most depressing circumstances, he formed new networks among cellmates for mutual support. His defiance against the state outside and inside the prison walls has greatly shaped the dynamics of Chinese church-state relations today, and Protestants worldwide often refer to martyrs like Watchman Nee to develop new paradigms for negotiating with anti-Christian forces.